A docência, seus saberes e a constituição do professor como profissional do ensino básico, técnico e tecnológico - Souza, Juscelino Pereira de (2018)
The objective of this research is to understand the actions performed by professional education teachers regarding their teaching methodologies in order to make an analytical reflection of the teaching knowledge in the classroom. The theme has relevance for bringing up the issue of the re-signification of the teaching action on present days. Technical knowledge and rationality, both characteristics of the teacher education process, contrast with an educational reality that demands update of the pedagogical practice at all times. Thus, teacher training should not only include technical knowledge, but also articulate work, science and culture in the teaching action. The methodological approach for this work consists of a qualitative research. Two techniques were used to collect data: questionnaire and interview. Data analysis sought to answer the following question: how does the teacher constitutes himself as a professional of the basic, technical and technological education in the classes of technical subjects? Oral and Written Narratives were chosen as analytical concepts. The narratives suggested that, at first, teachers’ constitution is based on their experience as students with their teachers and, as soon as they develop into teaching practices, their own experiences in the classroom and the contact with their own students raise doubts about the teaching and learning processes. Finally, the research subjects were teachers from Basic, Technical and Technological Education from a campus of the Federal Institute of Education, Science and Technology of Sao Paulo (IFSP), who had no pedagogical training. They all work with full time technical education, having had different trainings and having worked in different contexts and technical areas, resulting in a varied sample. As a result, it is expected to raise significant questions that contribute to the discussion on the training and professional knowledge of teachers on present days.